Minocycline and aspirin in the treatment of bipolar depression: a protocol for a proof-of-concept, randomised, double-blind, placebo-controlled, 2×2 clinical trial. Issue 1 (22nd February 2012) - Savitz, Jonathan; Preskorn, Sheldon; Teague, T Kent; Drevets, Douglas; Yates, William; Drevets, Wayne
Abstract : Introduction: New medication classes are needed to improve treatment effectiveness in the depressed phase of bipolar disorder (BD). Extant evidence suggests that BD is characterised by neural changes such as dendritic remodelling and glial and neuronal cell loss. These changes have been hypothesised to result from chronic inflammation. The principal aims of the proposed research is to evaluate the antidepressant efficacy in bipolar depression of minocycline, a drug with neuroprotective and immune-modulating properties, and of aspirin, at doses expected to selectively inhibit cyclooxygenase 1 (COX-1). Methods and analysis: 120 outpatients between 18 and 55 years of age, who meet DSM-IV-TR criteria for BD (type I or II) and for a current major depressive episode will be recruited to take part in a randomised, double-blind, placebo-controlled, parallel-group, proof-of-concept clinical trial following a 2×2 design. As adjuncts to existing treatment, subjects will be randomised to receive one of the four treatment combinations: placebo-minocycline plus placebo-aspirin, active-minocycline plus placebo-aspirin, placebo-minocycline plus active-aspirin or active-minocycline plus active-aspirin. The dose of minocycline and aspirin is 100 mg twice daily and 81 mg twice daily, respectively. Antidepressant response will be evaluated by assessing changes in the Montgomery–Asberg Depression Rating Scale scores between baseline and the end of the 6-week trial. As secondary outcome measures, the anti-inflammatory effects of minocycline and aspirin will be tested by measuring pre-treatment and post-treatment levels of C reactive protein and inflammatory cytokines. Ethics and dissemination: Minocycline has been widely used as an antibiotic in doses up to 400 mg/day. Low-dose aspirin has been safely used on a worldwide scale for its role as an antithrombotic and thrombolytic. The study progress will be overseen by a Data, Safety and Monitoring Board, which will meet once every 6 months. Results of the study will be published in peer-reviewed publications. Trial registration number: Clinical Trials.gov: NCT01429272 .